A scheme of resource allocation and stability for peer-to-peer file-sharing networks - Li, Shiyong; Sun, Wei; E, Cheng-Guo; Shi, Lina (Zielona Góra: Uniwersytet Zielonogórski)
Peer-to-peer (P2P) networks offer a cost-effective and easily deployable framework for sharing content. However, P2P file-sharing applications face a fundamental problem of unfairness. Pricing is regarded as an effective way to provide incentives to peers to cooperate. In this paper we propose a pricing scheme to achieve reasonable resource allocation in P2P file-sharing networks, and give an interpretation for the utility maximization problem and its sub-problems from an economic point of view.
Keywords: peer-to-peer networks; fairness; pricing; stability; utility maximization